Engaged at the first sight! Anticipating your audience as a way to think critically in writing an argument - Mahmud Layan Hutasuhut; Honglin Chen; Erika Matruglio (Indonesian Journal of Applied Linguistics, 2023)
Critical thinking has been subject to various theoretical interpretations. Despite the differences, it has been perceived to principally build upon argumentation skills. One of the skills involves anticipation of the putative reader. This paper establishes an insight into how this knowledge can be grounded for timely reader anticipation to evidence the skills in thinking critically when constructing a written argument. It draws on the interaction of interpersonal meaning patterns from the discourse semantic level in selected sets of low and high achieving texts, with a focus on the macroThemes. The texts were collected from three time points: pre, mid and final pedagogic intervention periods, enacting Teaching and Learning Cycle (TLC) framework, a genre-based pedagogy, in a regular academic writing course. Text analysis employed tools from the APPRAISAL systems of the Systemic Functional Linguistics (SFL). The analysis focused on the deployment of ENGAGEMENT resources in each text’s macroTheme. Findings from the analysis revealed a developmental pathway from a non-specific to a predictive and heteroglossic macroTheme. Appropriate ENGAGEMENT resources began to be manipulated to anticipate the argument development and the unfolding of meanings throughout the text. Their deployment became more effective to inform the reader on how the argument would be organised and negotiated. Re-thinking critical thinking through a linguistic lens elucidated exactly which language resources were implicated to indicate some of its important elements, making them visible and accessible.